Academic and non-academic responsibilities and length of services: descriptive and correlation analyses / Noor Emilina Mohd Nasir... [et al.] - Mohd Nasir, Noor Emilina; Ahmad, Suraya; Mohamed, Norazamina; Awang, Yunita (Universiti Teknologi MARA, Negeri Sembilan, 2019)
The issue of overwork due to numerous responsibilities among academicians is getting a serious attention in educational literature. Academicians have to fulfil many responsibilities simultaneously, including teaching, conducting research, writing, publication, holding administrative posts, involvement in committees and community services, and other professional works which may improve the image of their university. Thus, the objectives of this study are to examine the academicians’ perceptions on their academic and non-academic responsibilities and investigate the relationship between the respondents’ length of service with academic workloads and administrative posts. This study has used self-administered questionnaires, which have been distributed to 391 lecturers from various faculties on the Campus of UiTM Cawangan Terengganu. Results obtained from 119 academicians have indicated that a majority of the respondents have chosento bein the teaching-and-learning track for their performance-evaluation purpose. This is consistent with the findings that they have spent most of their working hours to fulfil their academic workloads. In addition, the non-academic responsibilities have required them to work beyond office hours in performing their duties. Overall, the findings of this study have shown that most academicians have spent more time on the academic responsibilities. On the other hand, the correlation has revealed that the longer the length of service of the respondents, the more academic workloads will be given and the higher their chances to be appointed as administrators. This has implied that the academicians will be responsible for higher positions and a wide range of tasks as they become more experienced and at a senior level.